2009
DOI: 10.1016/j.bone.2009.04.044
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of vitamin D deficiency in children and adolescents with type 1 diabetes

Abstract: SummaryBackground: Vitamin D is important for bone health. An inadequate supply of vitamin D to the body is associated with a higher fracture risk in the elderly. Young adults with type 1 diabetes are reported to have a lower peak bone mass than healthy individuals, which could possibly lead to an increased fracture risk in the future. The prevalence of vitamin D deficiency in healthy young people is high. Thus, optimal supply of vitamin D may be of particular importance for bone health in children with type 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 34 publications
1
28
1
3
Order By: Relevance
“…This agrees with Bin Abbas et al, and Bener et al, who found that vitamin D deficiency was considerably higher in children with T1DM (84%, 90.67% respectively) [10,11]. Although, the prevalence in this study was higher than that reported by Janner et al, 2010 and Thnc et al, 2011 (60.5%, 28% respectively) [12]. This different prevalence in vitamin D deficiency given from different countries could be related to the variability of vitamin D deficiency definition, as well as geographical environment and latitude, skin color, nutritional, social habits and may be genetic influence.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This agrees with Bin Abbas et al, and Bener et al, who found that vitamin D deficiency was considerably higher in children with T1DM (84%, 90.67% respectively) [10,11]. Although, the prevalence in this study was higher than that reported by Janner et al, 2010 and Thnc et al, 2011 (60.5%, 28% respectively) [12]. This different prevalence in vitamin D deficiency given from different countries could be related to the variability of vitamin D deficiency definition, as well as geographical environment and latitude, skin color, nutritional, social habits and may be genetic influence.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of vitamin D deficiency in children and adolescents with T1DM is very variable among the studies [3,[10][11][12]. In the current study, 91.67% of the children and adolescents with T1DM were vitamin D deficient.…”
Section: Discussionmentioning
confidence: 55%
“…In our study 25(OH)D was significantly lower (mean ±SD of 7.88 ± 1.20 ng/mL) in patients, compared with 16.64 ± 7.83 ng/mL in the controls. Many recently published studies have found significantly lower levels of 25(OH)D in patients with diabetes compared with controls (6,8,10,26).…”
Section: Discussionmentioning
confidence: 96%
“…In the past decade, interest in diabetes mellitus and vitamin D metabolism has grown. Many epidemiological studies have found high prevalence of VDD in children with type 1 diabetes mellitus (TIDM), suggesting an association between the two (7)(8)(9)(10). Type 1 DM is an autoimmune disease with contribution from environmental insults in its causation (11).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of vitamin D deficiency was 60.5% in a Swiss study (22), 43% in an Australian study (23), approximately 25% in an Italian study (24), and 15% in a North American study (25).…”
Section: Discussionmentioning
confidence: 94%